2001
DOI: 10.1034/j.1600-0714.2001.300704.x
|View full text |Cite
|
Sign up to set email alerts
|

Some specific human leukocyte antigen (HLA)‐DR/DQ haplotypes are more important than individual HLA‐DR and ‐DQ phenotypes for the development of mucocutaneous type of Behçet’s disease and for disease shift from recurrent aphthous stomatitis to mucocutaneous type of Behçet’s disease

Abstract: The phenotype and haplotype frequencies of human leukocyte antigens (HLA)-DR and -DQ in 32 Chinese patients with the mucocutaneous (MC) type of Behçet's disease (BD) were calculated and compared with those in 310 healthy control Chinese and with those in 80 Chinese patients with recurrent aphthous stomatitis (RAS). We found that the phenotype frequency of HLA-DRw8 [corrected P (Pc)<0.005] and the haplotype frequencies of HLA-DRw8/DQw1 (Pc<0.005), -DRw8/DQw5(w1) (Pc<0.0005), -DRw12(5)/DQw1 (Pc<0.005), -DRw12(5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Since HLA B51 antigen is raised in some series of patients with Behçet's disease (Verity et al ., 1999), recognition of HLA antigen haplotypes in RAS may be predictive of subsequent development of Behçet's disease (Sun et al ., 2001), although others have produced evidence against a common disease spectrum between RAS and Behçet's syndrome (Porter et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Since HLA B51 antigen is raised in some series of patients with Behçet's disease (Verity et al ., 1999), recognition of HLA antigen haplotypes in RAS may be predictive of subsequent development of Behçet's disease (Sun et al ., 2001), although others have produced evidence against a common disease spectrum between RAS and Behçet's syndrome (Porter et al ., 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The role of DNA polymorphisms in serotonin transporter gene, endothelial nitric oxide synthase gene and cell adhesion molecule genes has also been considered (Alkhateeb et al 2013; Gallo et al 2012; Karasneh et al 2005, 2009; Kim et al 2003; Oksel et al 2006; Salvarani et al 2002; Victoria et al 2005; Wang and Wang 2000). Other researchers reported the correlation between the selected HLA allele and the increased risk of RAS and Behçet’s syndrome (Albanidou-Farmaki et al 2008; Challacombe et al 1977; Sun et al 2001). In patients with RAS, a higher incidence of HLA-A33, HLA-B35 and HLA-B81 (Wilhelmsen et al 2009), HLA-B12 (Lehner et al 1982), HLA-B51 (Özdemir et al 2009), HLA-DR7 and HLA-DR5 and lower incidence of HLA-B5 and HLA-DR4 (Albanidou-Farmaki et al 1988; Gallina et al 1985) was observed when compared to healthy controls.…”
Section: Genetic Predispositionmentioning
confidence: 98%
“…In some, but not all groups (Shohat‐Zabarski et al , 1992), there may be a negative association of RAS with MT2 and MT3 (now HLA‐DQ series). A comparison of HLA phenotypes of patients of Chinese origin established that the frequency of HLA‐DR5; DRw8; DQw1 were increased in mucocutaneous Behcet's disease, compared with RAS as well as haplotypes DR5/DRw1 and DRw8/DRw1 (Sun et al , 2001). There would seem to be no consistent significant association between RAS and any particular serologically determined HLA antigen haplotypes except possibly HLA‐B51 (Shohat‐Zabarski et al , 1992).…”
Section: Genetic Basismentioning
confidence: 99%